Medical Assistance in Dying in Canada: An Ethical Analysis of Conscientious and Religious Objections - Christie, Timothy; Sloan, John; Dahlgren, Dylan; Koning, Fred (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2016)
Background: The Supreme Court of Canada (SCC) has ruled that the federal government is required to remove the provisions of the Criminal Code of Canada that prohibit medical assistance in dying (MAID). The SCC has stipulated that individual physicians will not be required to provide MAID should they have a religious or conscientious objection. Therefore, the pending legislative response will have to balance the rights of the patients with the rights of physicians, other health care professionals, and objecting institutions.Objective: The objective of this paper is to critically assess, within the Canadian context, the moral probity of individual or institutional objections to MAID that are for either religious or conscientious reasons.Methods: Deontological ethics and the Doctrine of Double Effect.Results: The religious or conscientious objector has conflicting duties, i.e., a duty to respect the “right to life” (section 7 of the Charter) and a duty to respect the tenets of his or her religious or conscientious beliefs (protected by section 2 of the Charter).Conclusion: The discussion of religious or conscientious objections to MAID has not explicitly considered the competing duties of the conscientious objector. It has focussed on the fact that a conscientious objection exists and has ignored the normative question of whether the duty to respect one’s conscience or religion supersedes the duty to respect the patient’s right to life.